Astoria Fan sediments, DSDP site 174, Cascadia Basin: Hf-Nd-Pb constraints on provenance and outburst flooding - Prytulak, J; Vervoort, J; Plank, T; Yu, C (2006)
The Astoria submarine fan, located off the coast of Washington and Oregon, has grown throughout the Pleistocene from continental input delivered by the Columbia River drainage system. Enormous floods from the sudden release of glacial lake water occurred periodically during the Pleistocene, carrying vast amounts of sediment to the Pacific Ocean. Deep Sea Drilling Project (DSDP) site 174, located on the southern distal edge of the Astoria Fan, is composed of 879 m of terrigenous sediment. The section is divided into two major units separated by a distinct seismic discontinuity: an upper, turbidite fan unit (Unit I), and an underlying finer-grained unit (Unit II). Both units have overlapping ranges of Nd and Hf isotope compositions, with the majority of samples having εNd values of - 7.1 to - 15.2 and εHf values - 6.2 to - 20.0; the most notable exception is the uppermost sample in the section, which is identical to modern Columbia River sediment. Nd depleted mantle model ages for the site range from 2.0 to 1.2 Ga and are consistent with derivation from cratonic Proterozoic source regions, rather than Cenozoic and Mesozoic terranes proximal to the Washington-Oregon coast. The Astoria Fan sediments have significantly less radiogenic Nd (and Hf) isotopic compositions than present day Columbia River sediment (εNd = - 3 to - 4; [Goldstein, S.J., Jacobsen, S.B., 1987. Nd and Sr isotopic systematics of river water suspended material: implications for crustal evolution. Earth. Planet. Sci. Lett. 87, 249-265.]), and suggest that outburst flooding, tapping Proterozoic source regions, was the dominant sediment transport mechanism in the genesis and construction of the Astoria Fan. Pb isotopes form a highly linear 207Pb/204Pb-206Pb/204Pb array, and indicate the sediments are a binary mixture of two disparate sources with isotopic compositions similar to Proterozoic Belt Supergroup metasediments and Columbia River Basalts. The combined major, trace and isotopic data argue that outburst flooding was responsible for depositing the majority (top 630 m) of the sediment in the Astoria Fan. © 2006 Elsevier B.V. All rights reserved.